Analysis of Cardiopulmonary Endurance of Basketball Athletes Coached by Gayo Lues Regency - Syukriadi, Amanda; Putra, Sukardi; Zulfikar, Zulfikar; Fajrial, Jul; Isdarianti, Novi Lidya (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. This research aims to discover the description of cardiopulmonary endurance in basketball athletes trained by the Gayo Lues district, which will be carried out in 2023. This research is classified as quantitative research using a field test and measurement approach to components of cardiopulmonary endurance. Materials and Methods. The population in this study were all basketball athletes trained by the Gayo Lues district, totaling 23 athletes consisting of 10 male athletes and 13 female athletes who were taken using saturated sampling techniques. Data collection was carried out using the Harvard step test instrument. The data is then analyzed using average statistical analysis and frequency or percentage distribution analysis. Results. The research results found that the cardiopulmonary endurance ability of male athletes had an average value of 70.1 and was in the medium category. For female athletes, cardiopulmonary endurance was found to be 65.7 and was in the medium category. Conclusion. Based on the research findings, it can be concluded that the cardiopulmonary endurance ability of basketball athletes trained by Gayo Lues district, both male and female athletes, is still in the medium category.